2014
DOI: 10.1039/c4cp02622e
|View full text |Cite
|
Sign up to set email alerts
|

Non-radiative decay paths in rhodamines: new theoretical insights

Abstract: We individuate a photoinduced electron transfer (PeT) as a quenching mechanism affecting rhodamine B photophysics in solvent. The PeT involves an electron transfer from the carboxylate group to the xanthene ring of rhodamine B. This is finely modulated by the subtle balance of coulombic and non-classical interactions between the carboxyphenyl and xanthene rings, also mediated by the solvent. We propose the use of an electronic density based index, the so called DCT index, as a new tool to assess and quantify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 48 publications
7
66
1
Order By: Relevance
“…The computed S 1 states of RDs by TDDFT with GH GGA and meta‐GGA functionals are in the ππ* state and correspond to pure transitions from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO). This result is in accordance with those of previous theoretical studies . Figure shows the computed HOMO and LUMO of Rhod101 by TD‐B3LYP as an example, and both the HOMO and LUMO are localized on xanthene moiety.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The computed S 1 states of RDs by TDDFT with GH GGA and meta‐GGA functionals are in the ππ* state and correspond to pure transitions from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO). This result is in accordance with those of previous theoretical studies . Figure shows the computed HOMO and LUMO of Rhod101 by TD‐B3LYP as an example, and both the HOMO and LUMO are localized on xanthene moiety.…”
Section: Resultssupporting
confidence: 92%
“…Designing and development of new RDs are still in progress despite the fact that many chemically modified RDs are commercially available . Previous theoretical studies found that the lowest excitation energies of RDs are overestimated systematically at approximately 0.4 eV by TDDFT approximations . Savarese et al also reported that the TD‐B3LYP‐D/6‐31 + G(d,p)/CPCM calculated the lowest excitation energy of rhodamine 110 (R110) in aqueous solution (~2.63 eV) and reproduces the experimental data (2.49 eV) .…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…The electron density redistribution upon the excitation along The Journal of Physical Chemistry B Article the IRC path can be analyzed and described through densitybased indexes such as the D CT one, as also demonstrated in previous works. 6,41,42 In Figure 4 D CT values calculated along the IRC path are reported. The transition state region of the ESPT reaction represents the maximal charge separation Figures 2 and 4, it is clear that the highest energy arrangement of the reaction (namely the TS) corresponds to the configurational space characterized by the maximum D CT , and therefore by the highest charge transfer degree.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, these methodologies have been extensively applied to study ESPT reactions . Moreover, the same approach can be applied, with due care, to the analysis of nonradiative events …”
Section: Introductionmentioning
confidence: 99%